2015
DOI: 10.1016/j.devcel.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Adherens Junctions Revisualized: Organizing Cadherins as Nanoassemblies

Abstract: This Perspective considers how classical cadherin cell-cell adhesion receptors are organized at the nanoscale to generate lateral clusters. Recent advances in optical microscopy reveal that clustering constitutes a general feature of cadherin organization, but one that takes diverse forms. Here we consider the molecular mechanisms responsible for cadherin clustering and their functional implications. We frame our discussion in light of what is known about how nanoscale organization is conferred upon the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 120 publications
4
100
0
Order By: Relevance
“…In agreement with electron microscopy, high magnification confocal microscope analysis of N-cadherin staining revealed prominent disorganization of N-cadherin-containing AJCs in E14.5 Llgl1 cKO cortexes, even in the areas that maintained the integrity of the ventricular wall (Figure S4). Abnormal junctions may be the result from decreased levels of adherens junction proteins N-cadherin, α- and β-catenins, failure of cadherin-catenin protein complex formation, failure of cadherin-catenin complex delivery and retention at the plasma membrane, or failure of clustering and stabilization of adhesion complexes by association with the actin cytoskeleton (Yap et al, 2015). We found no differences in the total levels of cadherin and catenin proteins or in the cadherin-catenin complex formation in E14.5 Llgl1 cKO ENSCs (Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with electron microscopy, high magnification confocal microscope analysis of N-cadherin staining revealed prominent disorganization of N-cadherin-containing AJCs in E14.5 Llgl1 cKO cortexes, even in the areas that maintained the integrity of the ventricular wall (Figure S4). Abnormal junctions may be the result from decreased levels of adherens junction proteins N-cadherin, α- and β-catenins, failure of cadherin-catenin protein complex formation, failure of cadherin-catenin complex delivery and retention at the plasma membrane, or failure of clustering and stabilization of adhesion complexes by association with the actin cytoskeleton (Yap et al, 2015). We found no differences in the total levels of cadherin and catenin proteins or in the cadherin-catenin complex formation in E14.5 Llgl1 cKO ENSCs (Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, clustering of the core proteins into puncta may be associated with the formation of stable interactions with the cytoskeleton. For example, the stability of E-cadherin clusters at adherens junctions is dependent on the actin cytoskeleton (reviewed in Yap et al., 2015), and cortical actin activity also regulates the mobility of GPI-linked proteins in nanoclusters (Goswami et al., 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have shown that cadherin punctae formed by the clustering of E-cadherin along cell-cell boundaries can increase in size during the maturation of cell-cell junctions, and that they are important for cell-cell adhesion and force transmission in vivo (26,30). How E-cadherin molecules come together and form these punctae has been under intense investigation (31): Some studies have suggested that E-cadherin molecules are able to move along lateral membranes (32, 33), and one of the common themes emerging is the importance of the cortical actin cytoskeleton in their formation (26,31).Cdh2 (N-cadherin) adhesive junctions play an important role in mechanical coupling between cardiomyocytes (34, 35). Despite its potential importance, no detailed analysis has been carried out on the organization of Cdh2 during heart development.…”
mentioning
confidence: 99%